PERSEPSI, SIKAP, DAN TINGKAT KEPUASAN PETANI TERHADAP VARIETAS UNGGUL KEDELAI DI KABUPATEN KEBUMEN, JAWA TENGAH - Chanifah Chanifah; Joko Triastono; Fransicus Rudi Prasetyo Hantoro (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
Imported soybeans have dominated national soybeans for more than two decades. To reduce dependence on imported soybeans, efforts are needed to maximize national soybean production and productivity through technological innovation. Soybean high yielding varieties are one of the easiest technologies to be adopted by farmers. The assessment aims to evaluate perceptions, attitudes and satisfaction of farmers with the attributes of superior soybean varieties. The assessment was carried out using a survey method of soybean farmers totaling 32 people in The Kebumen Regency. High yielding soybeans varieties studied is Grobogan, Anjasmoro and Gema varieties. Attributes evaluated are plant performance, yield, soybeans price selling, easier seeds to obtain, harvest age, the suitability of seed size to demand and pest resistance. Farmers’ perceptions were mapped using perceptual mapping, farmer attitudes were analyzed using the Fishbein Multiattribute Model and farmer satisfaction was analyzed using the Customer Satisfaction Index (CSI). The results of the study showed that farmers had better perceptions, attitudes and satisfaction towards Grobogan and Anjasmoro varieties compared to Gema variety. Grobogan and Anjasmoro varieties were perceived as more excellent because they had more attractive plant diversity, higher production, easier seeds to obtain and more resistance to pests-diseases. Farmers showed a more accepting attitude to cultivating Grobogan and Anjasmoro varieties with Fishbein Multiattribute scores of 45.63 and 43.93, while the Gema variety only scored 39.64. Farmers have a higher level of satisfaction with Grobogan and Anjasmoro variety with CSI values of 52.11% and 50.37% compared to the Gema variety of 44.66%.